2019
DOI: 10.1002/ecs2.2724
|View full text |Cite
|
Sign up to set email alerts
|

The amphibian‐killing fungus in a biodiversity hotspot: identifying and validating high‐risk areas and refugia

Abstract: Amphibian chytridiomycosis, due to infection with the fungus Batrachochytrium dendrobatidis (Bd), has been associated with the alarming decline and extinction crisis of amphibians worldwide. It is essential for conservation management to identify regions with high or low suitability for Bd. We use a species distribution model to estimate the environmental suitability of Bd in the Chilean Winter Rainfall–Valdivian Forest biodiversity hotspot. Fourteen environmental variables were used as predictors in the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…The increased suitability for Bd in lowlands of Costa Rica may explain the enigmatic declines experienced by several amphibian species in regions that were thought to be unsuitable for Bd (below 1,000 m elevation; Bolaños, 2009; Chaves et al., 2014; Zumbado‐Ulate, Bolaños, Willink, & Soley‐Guardia, 2011). The suitable elevational range predicted for enzootic Bd in Costa Rica matched with the elevational range reported for enzootic Bd in Panama, Mexico, Colombia, and Chile (Bacigalupe et al., 2019; Bolom‐Huet, Pineda, Díaz‐Fleischer, Muñoz‐Alonso, & Galindo‐González, 2019; Flechas et al., 2017; Kilburn et al., 2010; Woodhams et al., 2008). The climatic variable contributions in our model (Table S1) also suggested that habitat suitability for enzootic Bd in Costa Rica is associated with seasonal climatic interactions across the year that favor or constrain Bd occurrence.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The increased suitability for Bd in lowlands of Costa Rica may explain the enigmatic declines experienced by several amphibian species in regions that were thought to be unsuitable for Bd (below 1,000 m elevation; Bolaños, 2009; Chaves et al., 2014; Zumbado‐Ulate, Bolaños, Willink, & Soley‐Guardia, 2011). The suitable elevational range predicted for enzootic Bd in Costa Rica matched with the elevational range reported for enzootic Bd in Panama, Mexico, Colombia, and Chile (Bacigalupe et al., 2019; Bolom‐Huet, Pineda, Díaz‐Fleischer, Muñoz‐Alonso, & Galindo‐González, 2019; Flechas et al., 2017; Kilburn et al., 2010; Woodhams et al., 2008). The climatic variable contributions in our model (Table S1) also suggested that habitat suitability for enzootic Bd in Costa Rica is associated with seasonal climatic interactions across the year that favor or constrain Bd occurrence.…”
Section: Discussionsupporting
confidence: 67%
“…The bars under each map show suitability by elevation with black indicating the predicted percentage of climatic suitability for Bd. Altitudinal bars display belts of 500 m except the seventh bar that shows all elevations above 3,000 m (1 = 0-500 m; 2 = 500-1,000 m; 3 = 1,000-1,500 m, 4 = 1,500-2,000 m; 5 = 2,000-2,500 m; 6 = 2,500-3,000 m; 7 = 3,000-3,820 m) the elevational range reported for enzootic Bd in Panama, Mexico, Colombia, and Chile (Bacigalupe et al, 2019;Bolom-Huet, Pineda, Díaz-Fleischer, Muñoz-Alonso, & Galindo-González, 2019;Flechas et al, 2017;Kilburn et al, 2010;Woodhams et al, 2008). The climatic variable contributions in our model (Table S1) confirmed that enzootic Bd is currently infecting species that exhibit multiple life-history traits across all elevations.…”
Section: Geographic Distribution Of Bdmentioning
confidence: 81%
See 1 more Smart Citation
“…Once signed by the environment authorities of both countries, the strategy will facilitate interdisciplinary and international working amongst public agencies. Another area in which both countries can take action involves animal health departments, with the enforcement of amphibian import regulations and the implementation of biosecurity protocols aimed at limiting the spread of B. dendrobatidis (and other invasive species) both at national and local levels (Valenzuela-Sánchez et al, 2018; Bacigalupe et al, 2019). Official recognition of the strategy is also relevant for establishing nation-wide conservation education programmes.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the more than 96 species of Atelopus are now extinct or in decline, mainly because of infection by the pathogenic fungus Batrachochytrium dendrobatidis ( Bd ) for those inhabiting mid to high elevations and due to habitat loss for lowland species (La Marca et al., 2005). Despite Bd being generally less severe in warmer lowland areas (Bacigalupe et al., 2019), these portions of the landscape in Amazonia are often deforested for human use and disturbed areas seem to be suitable for Bd invasion in central Amazonia (Becker, Rodriguez, Lambertini, Toledo, & Haddad, 2015), and other tropical regions (Bolom‐Huet, Pineda, Días‐Fleischer, Muñoz‐Alonso, & Galindo‐González, 2019).…”
Section: Introductionmentioning
confidence: 99%